1879–80 Va. Acts 104, ch. 5, § 4, pt. 19 - (:unkn) unknown (General Publisher, 1879)
To direct the location of all buildings for storing gun-powder or other combustible substances; to regulate the sale and use of gunpowder, fire-crackers, fire-works, kerosene oil, nitroglycerine . . . the discharge of firearms
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER